Preoperative Paravertebral Block and Chronic Pain after Breast Cancer Surgery: A Double-blind Randomized Trial. (December 2021) - Albi-Feldzer, Aline; Dureau, Sylvain; Ghimouz, Abdelmalek; Raft, Julien; Soubirou, Jean-Luc; Gayraud, Guillaume; Jayr, Christian
Abstract : Background: The effectiveness of paravertebral block in preventing chronic pain after breast surgery remains controversial. The primary hypothesis of this study was that paravertebral block reduces the incidence of chronic pain 3 months after breast cancer surgery. Methods: In this prospective, multicenter, randomized, double-blind, parallel-group, placebo-controlled study, 380 women undergoing partial or complete mastectomy with or without lymph node dissection were randomized to receive preoperative paravertebral block with either 0.35 ml/kg 0.75% ropivacaine (paravertebral group) or saline (control group). Systemic multimodal analgesia was administered in both groups. The primary endpoint was the incidence of chronic pain with a visual analogue scale (VAS) score greater than or equal to 3 out of 10, 3 months after surgery. The secondary outcomes were acute pain, analgesic consumption, nausea and vomiting, chronic pain at 6 and 12 months, neuropathic pain, pain interference, anxiety, and depression. Results: Overall, 178 patients received ropivacaine, and 174 received saline. At 3 months, chronic pain was reported in 93 of 178 (52.2%) and 83 of 174 (47.7%) patients in the paravertebral and control groups, respectively (odds ratio, 1.20 [95% CI, 0.79 to 1.82], P = 0.394). At 6 and 12 months, chronic pain occurred in 104 of 178 (58.4%) versus 79 of 174 (45.4%) and 105 of 178 (59.0%) versus 93 of 174 (53.4%) patients in the paravertebral and control groups, respectively. Greater acute postoperative pain was observed in the control group 0 to 2 h (area under the receiver operating characteristics curve at rest, 4.3 ± 2.8 vs. 2.9 ± 2.8 VAS score units × hours, P < 0.001) and when maximal in this interval (3.8 ± 2.1 vs. 2.5 ± 2.5, P < 0.001) but not during any other interval. Postoperative morphine use was 73% less in the paravertebral group (odds ratio, 0.272 [95% CI, 0.171 to 0.429]; P < 0.001). Conclusions: Paravertebral block did not reduce the incidence of chronic pain after breast surgery. Paravertebral block did result in less immediate postoperative pain, but there were no other significant differences in postoperative outcomes. Abstract : More than 350 study participants undergoing mastectomy were randomized to either paravertebral blocks with ropivacaine or saline injections. Both groups received multimodal analgesia. Although paravertebral block using ropivacaine had a small analgesic effect in the immediate postoperative period, no differences in pain 3, 6, and 12 months after surgery were detected.